ショウワキチ ニ オケル エットウタイイン ノ エイヨウ セッシュリョウ ニ ツイテ : ダイ39ジ エットウタイ ノ ショクジ キロク ノ カイセキ - 中尾, 美千代; ナカオ, ミチヨ; 大野, 義一朗; オオノ, ギイチロウ; 小澤, 美貴; オザワ, ミキ; 山本, 隆子; ヤマモト, タカコ; 森本, 武利; モリモト, タケトシ; Nakao, Michiyo; Ohno, Giichiro; et al. (2002)
P(論文) 第39次越冬隊の医療隊員が、越冬期間中に自分自身の摂取した食事をすべてデジタルカメラで記録した。このデジタルカメラの画像から摂取した食品重量を推定して栄養分析を行った。エネルギー摂取量は日本人の栄養所要量に示される生活活動強度Iのエネルギー所要量よりも若干高値を示したが、1月の摂取量は有意に高値を示した。PFC比からみるとたんぱく質および脂肪の比率が高く、炭水化物比が低い傾向を認めた。特に不足を認めた栄養素はビタミンCと食物繊維とカルシウムで、これらについては食材の確保や保管などの問題が関与すると考えられ、ビタミン剤等による補給の必要性を示すものである。 The nutritional supply of wintering personnel at Syowa Station was analyzed throughout the year 1998. Analysis was performed employing digital pictures of food chosen and consumed by one of the station personnel (medical doctor: male) throughout the year. Food consumption was estimated from the pictures, and energy and nutrient consumption were determined using food-content software. The average daily food value was calculated for every month, and compared with the nutritional standard for normal Japanese citizens. Mean energy consumption was significantly higher in January, when outdoor activities were required, and significantly lower in June, when outdoor activities were lower due to the polar night. Protein (P) and fat (F) intake were higher and carbohydrate (C) was less than the Recommended Daily Amounts for Japanese throughout the year. The consumption of Vitamin C was highest in April, and showed lower values after June. Sodium chloride intake showed an increasing trend throughout the year, possibly due to increased use of preserved food. The supply of fiber was about 50% of the recommended amount for Japanese, possibly due to the limited supply of fresh vegetables and fruit. departmental bulletin paper